A supply chain analysis of the mussel industry in Jiabong, Samar. - Abarracoso, Tessie A.; Pabunan, Joanne B.; Tagoctoc, Vanessa T. (Tessie A. Abarracoso, Joanne B. Pabunan, 2019)
The municipality of Jiabong is known for its green mussels, Perna viridis (Linnaeus, 1758). It is the top supplier of mussels in the region, making it the Mussel Capital of Eastern Visayas and the major source of livelihood for the people of Jiabong since the 1970s.